Design and Validation of the Phase-Compensated Long-Range Sub-THz VNA-Based Channel Sounder - Lyu, Yejian; Mbugua, Allan Wainaina; Olesen, Kim; Kyosti, Pekka; Fan, Wei (IEEE antennas and wireless propagation letters, 2021)
This letter presents the first vector network analyzer based subterahertz (sub-THz) phase-compensated channel sounder at 220-330 GHz using radio-over-fiber techniques that could enable long-range phase-coherent measurements. The optical cable solution enables long-range channel measurements at sub-THz bands, since it can effectively minimize the cable loss. This letter also proposes a novel phase compensation scheme to stabilize the phase variations introduced by optical fiber of the channel sounder to enable its application in multichannel/antenna measurements. This proposed channel sounder is validated in back-to-back measurements under two optical cable conditions, i.e., with presence of thermal changes and mechanical stress. The phase variation introduced by the cable effects in the system is shown to be over 400^° in 220-330 GHz, compared to 15^° at 220-288 GHz and 37^° in 288-330 GHz after compensation, respectively, demonstrating the robustness and effectiveness of the developed channel sounder in practice. The developed system, which has a dynamic range of 106.7 dB, can support measurement range up to 300 m (limited by the optical cable length in our system and subject to over-the-air signal transmission loss in practical environment).